Obtencion jabón a partir de aceites de elaeis guineensis (palma aceitera), helianthus annuus (girasol), plukenetia volúbilis linneo (aceite sacha inchi), y la adición de scoparia dulsis (teatina) como agente antimicrobiano - Vallejo Banchen, Ana Gabriela (2015)
This research is based evaluate 3 different types of oils: Oils of Elaeis guineensis (Palm Oil), Helianthus Annuus (sunflower), Plukenetia Volubilis Linnaeus (Sacha oil weigh up) with scoparia dulsis (teatina) in the development of soap with antibacterial properties. Basically this research seeks to address the problem arising out of the ignorance of the effect of different products with antimicrobial properties as the teatina in utilization in the development of products with different components, to produce various by-products of fatty common usage, such as toiletries added of properties Antimicrobial, for this reason was raised as objective Obtain soap from different types of fat oil palm (Elaeis guineensis), oil sunflower (Helianthus annuus), Sacha oil weigh up (Plukenetia volubilis Linnaeus), and the addition of Teatina (Scoparia dulsis) as an antimicrobial agent. This research required of 6 treatments with 3 replicates to determine which of the concentration levels of teatina is best for the inhibition of bacteria strectococcus aureus and which of the oils studied reported best features in the development of the product, for this was evaluated as variables in the study: pH, acidity, level of foam, mass, and acceptability. To determine which of the soaps has better features. The experiment was performed, using a factorial arrangement TO * B, where the factor to evaluated the types of oils and B the concentration of teatina. For the separation of mean levels of the treatments went to the significance test Tukey (p <0.5 ). ...